THERMODYNAMIC DATA FROM REDOX REACTIONS AT HIGH TEMPERATURES. VI. THERMODYNAMIC PROPERTIES OF COO-MNO SOLID SOLUTIONS FROM EMF MEASUREMENTS - Pownceby M.I.; O'Neill H.St.C. (My University, 2000)
Activities of CoO in (Co,Mn)O solid solutions in contact with metallic Co have been determined on ten compositions ranging from 0.12 to 0.84 XCoO in order to calibrate the divariant equilibrium between (Co,Mn)O oxide solutions and Co metal as an oxygen fugacity sensor for application in experimental petrology. Experiments were conducted over the temperature range 900-1300 K at 1 bar, using an electrochemical technique with oxygen-specific calcia-stabilized zirconia (CSZ) electrolytes. Co + CoO or Fe + FeO was used as the reference electrode. Compositions of the (Co,Mn)O solid solutions were measured after each run by electron microprobe, and these were checked for internal consistency by measuring the lattice parameter by X-ray diffraction. Activity-composition relations were fitted to the Redlich-Kister formalism. (Co,Mn)O solid solutions exhibit slight positive deviations from ideality, which are symmetrical (corresponding to a regular solution mixing model) across the entire composition range with A0G = 3690(±47) Jmol-1. Excess entropies and enthalpies were also derived from the emf data and gave Sex=0.77(±0.08) JK-1 mol-1 and Hex=4558(±90) Jmol-1 respectively. The experimental data from this study have been used to formulate the (Co,Mn)O/Co oxygen fugacity sensor to give an expression: where μO2CoCoO=-492,186 + 509.322 T - 53.284 T lnT + 0.02518 T2, taken from O'Neill and Pownceby (1993).